Key Anatomical Clarifications for the Marginal Mandibular Branch of the Facial Nerve: Clinical Significance for the Plastic Surgeon. (16th December 2020) - Marolt, Clayton; Freed, Blair; Coker, Charles; Steele, Robert; Johnson, Kenneth; Arellanes, Russell; Gordon, Victoria; Wright, Barth; Stephens, Robert; Surek, Christopher C
Abstract: Background: The marginal mandibular branch (MMBr) of the facial nerve is the least likely to recover from injury due to infrequent anastomosis with other branches. The MMBr has been described as coursing superior to the inferior border of the mandible. However, studies have reported variations in its location in embalmed and fresh specimens. It has been postulated that the embalming process may effect its anatomic position. Objectives: The aim of this study was to re-evalulate the location of the MMBr relative to the inferior border of the mandible in both fresh and embalmed cadavers, and investigate variation in its position with sex, side of the face, and age. Methods: Superficial fascial planes were dissected to reveal the MMBr and its anatomic relations. Distance between the most inferior branch of the MMBr and the antegonial notch were measured bilaterally. The most inferior position of the MMBr between the antegonial notch and gonion was measured. Fresh heads were used as a comparison, with an additional measurement taken of the distance between the MMBr and the gonial angle. Results: The MMBr was located inferior to the border of the mandible (90.3%) more often than above (9.6%). No significant differences were found between fresh and embalmed cadavers, sex, side of body, or age ( P > 0.05). No significant difference was found between intact cadavers and fresh heads ( P > 0.05). Conclusions: This study confirms and describes reliable landmarks for safety zones for the MMBr during plastic and reconstructive surgery of the lower face and upper neck. These data add reliability to studies that have investigated nerve locations in embalmed cadavers.